Vyron Antoniadis. Knossos and the Near East / Barbara Bohen. Kratos and Krater / Xenia Charalambidou and Catherine Morgan (eds). Interpreting the Seventh Century BC - Whitley, James (Journal of Greek Archaeology, 2020)
The Aegean and Mediterranean world between 1000 and 600 BCE (the Early Iron Age and the earliest part of the Archaic period) continues to attract considerable scholarly attention. And for good reason. The period between 1000 and 600 BCE is the formative period in Greek history, where those institutions we most firmly associate with Greek culture (the sanctuary, the polis, the alphabet and the literature that resulted from it) took their definitive form. It is also a period where investigation has to be undertaken primarily by archaeologists.